Post Cementation Sensitivity of Conventional Glass Ionomer Cement as a Luting Material - Ambreen Usmani, Awais Khan, Muhammad Waqas, Maria Naseem, Sana Mubarak, Mehwish Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Was to determine the frequency of post cementation sensitivity of glass ionomer cement (GIC). Materials and methods: This cross sectional study included 86 participants with age from 20 to 65 years, both males and females, Pakistani nationals, abutment teeth with vital pulp without attrition, erosion or abrasion and no pulp capping agents used. The participants who had undergone Orthodontic treatment in last three months, or used bleach, having periodontal surgery, using medication like carbamazepine or analgesics and Psychiatric patients were excluded. Participants were asked about post cementation sensitivity on call at 24 hours. Descriptive statistics were calculated. Chi-square test was applied for comparison among gender and age groups. Results: The mean age was 40.27±10.68 years. The females were 33 (38.37%) and males were 53(61.63%). Postcementation sensitivity was found in 10(11.63%) participants. The most common type of sensitivity was moderate present in 5(5.81%) followed by severe present in 3(3.49%) and least was mild present in 2(2.23%) participants. The frequency of postcementation sensitivity was higher in younger age (n=7, 35%) than older ages statistically (p=0.003). Similar results were found for type of postcementation sensitivity (p=0.046). Conclusion: The frequency of post cementation sensitivity is quiet higher and most frequent in young ages. Keywords: Post cementation sensitivity, glass ionomer cement, luting agent.